Diversity in Marketing System Assortments. (September 2015) - Layton, Roger A.; Duan, Zhirong
An assortment offered by a marketing system can be defined as a set of separable or distinguishable products, services, experiences and ideas, or aggregates thereof, assembled in response to or anticipation of customer demand. As marketing systems form and grow, assortment diversity often increases, raising concerns about excessive or inadequate customer choice. Changing assortment diversity may also point to deeper issues of emerging dominance and inequality, to concerns about marketing system resilience in the face of environmental turbulence, and to issues of access to vulnerable segments. After highlighting the contribution of Alderson in emphasising diversity in buyer and seller heterogeneity, we note the differences between offered, accessible, desired, acquired and accumulated assortments, and the difficulties in establishing categories or types in the measurement of assortment. Variety, disparity, balance, and association are identified as providing measures of assortment diversity. We then considers the ways in which such measures may be pointers to underlying marketing system characteristics, including the offer of too much or too little choice, problems of stability in the face of external or internal change, system resilience or capacity to adapt to change, and issues around assortment and quality of life. We conclude with suggestions as to further research into assortment diversity and marketing system characteristics.